Islam sebagai Ideologi Emansipatoris: Telaah Pemikiran Teologi Kontemporer Ali Syariati (1933–1977 M) - Harianto, Budi; Nurul Syalafiyah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study examines the thought of Ali Shariati (1933–1977) as a contemporary Islamic intellectual who emphasized Islam as an emancipatory ideology. The study aims to uncover Shariati’s contributions to the development of theological discourse, his role in Iran’s socio-political liberation, and the implications of his thought for the responsibilities of Muslim intellectuals. The research employs a qualitative methodology with a historical-philosophical approach, tracing Shariati’s intellectual biography, mapping the influences shaping his ideas, and interpreting the ideological meaning of his thought within the socio-political context of Iran. The findings reveal that Shariati integrated the concepts of ummah and imamah as the foundation of revolutionary theology, stressed the social responsibility of intellectuals, and utilized his writings and lectures as instruments for social and political transformation. His thought not only influenced young generations and students in Iran but also offered theoretical and practical contributions to understanding Islam as an agent of change and liberation.